Retinal blood flow in diabetic retinopathy. Issue 6855 (19th September 1992) - Patel, V.; Rassam, S.; Newsom, R.; Wiek, J.; Kohner, E.
Abstract : OBJECTIVES–(a) To report on the basic parameters of retinal blood flow in a population of diabetic patients with and without retinopathy and non-diabetic controls; (b) to formulate a haemodynamic model for the pathogenesis of diabetic retinopathy from this and other studies. DESIGN–Laser-Doppler velocimetry and computerised image analysis to determine retinal blood flow in a large cross sectional study. SETTING–Diabetic retinopathy outpatient clinic. SUBJECTS–24 non-diabetic controls and 76 diabetic subjects were studied (63 patients with insulin dependent diabetes, 13 with non-insulin dependent diabetes). Of the diabetic subjects, 12 had no diabetic retinopathy, 27 had background retinopathy, 13 had pre-proliferative retinopathy, 12 had proliferative retinopathy, and 12 had had pan-retinal photocoagulation for proliferative retinopathy. MAIN OUTCOME MEASURES–Retinal blood flow (microliters/min) and conductance (rate of flow per unit of perfusion pressure). RESULTS–In comparison with non-diabetic controls (9.52 microliters/min) and diabetic patients with no diabetic retinopathy (9.12 microliters/min) retinal blood flow was significantly increased in all grades of untreated diabetic retinopathy (background 12.13 microliters/min, pre-proliferative 15.27 microliters/min, proliferative 13.88 microliters/min). There was a significant decrease in flow after pan-retinal photocoagulation in comparison with all the other groups studied (4.48 microliters/min). Conductance of the retinal circulation was higher in the untreated diabetic retinopathy groups. These results were independent of age, sex, type of diabetes, duration of diabetes, glycated haemoglobin concentration, blood glucose concentration, blood pressure, and intraocular pressure. CONCLUSIONS–Retinal blood flow is significantly increased in diabetic retinopathy in comparison with non-diabetic controls and diabetic subjects with no retinopathy. This has implications for controlling hypertension and hyperglycaemia as a strategy in reducing morbidity from diabetic retinopathy.